Incentive effects of risk pooling, redistributive and savings arrangements in unemployment benefit systems: Evidence from a job-search model for Brazil - David A. Robalino; Eduardo Zylberstajn; Juan David Robalino (Institute for the Study of Labor (IZA), 2011)
We develop a model of job search and use it to assess the effects that the Brazilian unemployment benefit system has on exit rates from unemployment. In our setup, unemployed workers receive job offers from the formal and informal sectors and decide whether to accept them or wait. Only jobs in the formal sector come with unemployment benefits. After incorporating the rules of the Brazilian unemployment benefit system we estimate the parameters of the model using its labor force survey (a rotating panel). Key parameters determining model dynamics are: the distribution of wage offers for each individual; the observed probabilities of separation from formal and informal jobs; and the unobserved job offers arrival rates. The results show that, in general, workers eligible for unemployment benefits also have higher offer rates - their unobserved characteristic are correlated with more job opportunities. Policy simulations ten suggest that the risk pooling and savings component of the unemployment benefit system have small effects on the probabilities of remaining unemployed. The main effect of both schemes is to reduce transitions into informal jobs. The effects are larger for unskilled workers, particularly women. The simulations also show that current effects are conditioned on the design of the system. More generous unemployment benefits, for instance, could substantially increase the share of workers who remain unemployed. In addition, asking workers to contribute to finance unemployment benefits would reduce formal employment.
urn:nbn:de:101:1-201104113495
Keywords: J63; J64; J65; 330; social protection; unemployment insurance; labor market transitions; job-search models; structural estimations; Arbeitslosenversicherung; Arbeitsuche; Berufseinstieg; Informeller Sektor; Brasilien